Proceedings of the 51st Hawaii International Conference on System Sciences 2018
DOI: 10.24251/hicss.2018.506
|View full text |Cite
|
Sign up to set email alerts
|

Analytics in the Pursuit of Knowledge: Adapting the Knowledge Pyramid

Abstract: Advances in storage leading to the Internet of Things (IOT) and Big Data has exponentially increased the Data aspect of the traditional Knowledge Pyramid-Data-Information-Knowledge-Wisdom (DIKW). This paper presents an adaptation of the Knowledge Pyramid as an Analytics Pyramid in which Time is posited to represent Wisdom as the pinnacle achievement when pursuing knowledge. Analogies of the DIKW are presented from the Analytics Pyramid as Description-Aggregation-Modeling-Time. Implementing the premise of the A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
(46 reference statements)
0
1
0
Order By: Relevance
“…Other researchers, such as (Dilla et al, 2010;Dilla & Raschke, 2015;Huber et al, 2018;Phillips-Wren & McKniff, 2020), found that IDV improves decision-makers' perceptions, decisions and impact in various contexts, from finance to healthcare operations. These studies highlight the importance of experiential knowledge of non-technical decision makers (Freeze, 2018).…”
Section: Prior Studies On Va For Non-technical Decision Makersmentioning
confidence: 93%
“…Other researchers, such as (Dilla et al, 2010;Dilla & Raschke, 2015;Huber et al, 2018;Phillips-Wren & McKniff, 2020), found that IDV improves decision-makers' perceptions, decisions and impact in various contexts, from finance to healthcare operations. These studies highlight the importance of experiential knowledge of non-technical decision makers (Freeze, 2018).…”
Section: Prior Studies On Va For Non-technical Decision Makersmentioning
confidence: 93%